Identification of halal labels on primary and secondary drug packaging at RSUD Dr. Soegiri Lamongan - Khoiro, Niswatin; Kusumanegara, Sri Bintang Sahara Mahaputra; Handayani, Riana Prastiwi (Journal of Halal Science and Research, 2025)
The majority of religions practiced by residents in the Lamongan area are Islam. In Islam, it is commanded to seek treatment with what is halal and is prohibited from seeking treatment with what is haram. Consumers cannot meet the manufacturer directly, but they must pay attention to the halal label on the drug packaging to consider their choices. This study aims to determine the percentage of drugs with the halal logo at Dr Soegiri Lamongan. This research used an observational design with samples of oral medication packaging at Dr. RSUD. Soegiri Lamongan and use a purposive sampling technique. The instrument used is an observation sheet. The research results showed that from 395 items of oral drugs at RSUD Dr Soegiri Lamongan had a halal label 97 (25%) consisting of capsule preparations of 12 (22%) medicinal items, caplets 6 (12%) medicinal items, tablets 65 (27%) medicinal items, dry syrup 1 (10%) items of medicine, suspension 4 (40%) items of medicine, elixir 1 (100%) items of medicine, drops 2 (25%) items of medicine, and syrup 6 (35%) items of medicine. In contrast, those that do not have a halal label are 298 (75%) oral drugs. The McNemar Test results showed a value of p = 0.000 with a significance value of p < 0.05 for all drugs and oral solid drugs. Meanwhile, the results of the McNemar test on oral liquid drugs show a value of p = 1.000 with a significance value of p > 0.05. Thus, many oral drugs still do not have a halal label on their packaging. Thus, many oral drugs still do not have a halal label on their packaging. However, these drugs are not necessarily haram. The certification process takes quite a long time, and the critical points for halal medicine, which lie in the ingredients, processing, packaging, and storage, are important things in the halal certification process to obtain a halal medicine label.   Keywords: Critical points, Drug, Halal label, Packaging.